Do ground source heat pumps challenge the dominant position of district heating in the Swedish heating market?. (1st May 2020) - Åberg, Magnus; Fälting, Lars; Lingfors, David; Nilsson, Annica M.; Forssell, Anders
Abstract: In urban areas, district heating (DH) has a dominant position in the Swedish heating market. Historically, DH has met almost no competition from other heat supply technologies. However, ground source heat pumps (GSHPs) have become more economically feasible and indications suggest that they are potentially replacing DH. This study investigates if GSHPs present a competitor to DH and what obstacles for GSHP that exist in urban areas. The investigation is based on a questionnaire study and calculations that illustrate limitations of replacing DH with GSHPs. The analysis employs theories of natural monopolies, market entry barriers, and common pool resources. A competition index is introduced to indicate competition between GSHPs and DH. The study concludes that GSHP are currently not strong competitors to DH in Sweden, and that a full replacement of DH with GSHPs is not realistic due to the large areas needed for energy wells. In urban areas, zones of competition between GSHPs and DH and zones of technological monopoly for DH are identified. Policies that regulate the distance between energy wells affect the competitiveness between the two technologies, but are necessary in order to avoid net cooling of the ground.